2014
DOI: 10.3402/gha.v7.23623
|View full text |Cite
|
Sign up to set email alerts
|

The first 500 days of life: policies to support maternal nutrition

Abstract: Background: From conception to 6 months of age, an infant is entirely dependent for its nutrition on the mother: via the placenta and then ideally via exclusive breastfeeding. This period of 15 months Á about 500 days Á is the most important and vulnerable in a child's life: it must be protected through policies supporting maternal nutrition and health. Those addressing nutritional status are discussed here. Objective and design: This paper aims to summarize research on policies and programs to protect women's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
56
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 33 publications
0
56
0
10
Order By: Relevance
“…The other studies also strongly recommended that the optimal nutrition of children under two years of age, it is considered important that they be exclusively breastfed for the first 6 months before being given complementary food [26]. In many studies, it is indicated that duration of exclusive breastfeeding (>6 months) and the age for starting complementary feeding is significantly associated with higher weight, length, and lower probability of stunting, wasting and infections [26][27][28][29]. This could be due to lack of essential nutrients from the breast milk during the first six months of life and later.…”
Section: Discussionmentioning
confidence: 99%
“…The other studies also strongly recommended that the optimal nutrition of children under two years of age, it is considered important that they be exclusively breastfed for the first 6 months before being given complementary food [26]. In many studies, it is indicated that duration of exclusive breastfeeding (>6 months) and the age for starting complementary feeding is significantly associated with higher weight, length, and lower probability of stunting, wasting and infections [26][27][28][29]. This could be due to lack of essential nutrients from the breast milk during the first six months of life and later.…”
Section: Discussionmentioning
confidence: 99%
“…A child's development depends entirely on the mother's nutritional status during fetal life and the first six months of life [2]. Current knowledge shows the adverse effects of maternal malnutrition on their health and that of their children [3].…”
Section: Introductionmentioning
confidence: 99%
“…The implications for child health and development with respect to an anaemic caregiver have also been recognised (38) . Therefore, prevention strategies should target adolescent girls and women of reproductive age to eliminate or reduce the burden of anaemia before entering into the higher nutritional demands of pregnancy (39)(40)(41) . A continuum in interventions is required during the reproductive period for the benefit to reach the offspring.…”
Section: Discussionmentioning
confidence: 99%